2000
DOI: 10.1159/000007822
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Acute Murine Dextran Sodium Sulphate Colitis: Cytokine Profile and Dose Dependency

Abstract: Background/Aims: In our experience with the acute murine dextran sodium sulphate (DSS) model of experimental colitis, we noted both interstrain and interanimal variations in daily water consumption. One might critically question whether observed differences in injuries are just a dose dependency phenomenon reflecting variations in DSS intake. To clarify this important topic, we performed a dose and concentration dependency study of DSS in Balb/c mice. We also determined Th1 and Th2 cytokine levels to compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
276
3
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(314 citation statements)
references
References 27 publications
26
276
3
5
Order By: Relevance
“…5C). Although DSS-induced chronic colitis has been reported to be a Th1-dominant disease [6,31], we could not confirm significant Th1 cell infiltration in situ [32] by day 5. Since acute DSS-induced colitis could be induced even in SCID mice, which lack T cells [22], it is likely that DSS directly injures the epithelium.…”
Section: Discussioncontrasting
confidence: 81%
“…5C). Although DSS-induced chronic colitis has been reported to be a Th1-dominant disease [6,31], we could not confirm significant Th1 cell infiltration in situ [32] by day 5. Since acute DSS-induced colitis could be induced even in SCID mice, which lack T cells [22], it is likely that DSS directly injures the epithelium.…”
Section: Discussioncontrasting
confidence: 81%
“…61,62 The T H 1 cytokines encompass the cytokine profile of acute murine DSSinduced colitis (INF-␥, TNF-␣, and IL-1␤). 63 In T H 1 cells, the recruitment of phospho-CREB is significantly higher than in T H 2 cells. 64 In the present study, we demonstrated that BCP treatment decreased DSS-induced CREB activation, which may be linked to decreased T H 1 cytokines, such as INF-␥, and the enhancement of T H 2 cytokines, namely IL-4.…”
Section: Discussionmentioning
confidence: 90%
“…DSS-induced experimental colitis model is still regarded as a reliable model for the IBD cellular and molecular studies (4). It has been reported that the Th1 cytokine response and histological changes in acute DSSinduced colitis model resemble those observed in human IBDs (5).…”
Section: Introductionmentioning
confidence: 83%